Presenting your research : conferences, symposiums, poster presentations and beyond - Becker, Lucinda (London : SAGE Publication Ltd., 2014)
For many researchers, the need to present relevant and engaging material in the most effective way in an unfamiliar setting presents a potential barrier to their success as professionals. This handy guide tackles the obstacles to effective and successful presentations, considering the range of material which might be presented, the occasions which suit different types of material and the skills needed to present research in a way that is engaging and persuasive.
One. Introduction -- Two..When and where should I give a paper? -- Three..Calls for papers: how the conference system works -- Four..Preparing an abstract/outline/synopsis -- Five..Conference paper or presentation? -- Six..Choosing material for an event -- Seven..Preparing your material -- Eight..Presentation aids -- Nine..Preparing to present -- Ten..Delivering your material -- Eleven..Using your nerves -- Twelve..Handling questions -- Thirteen..Poster presentations -- Fourteen..Making the most of the presentation opportunity.
Includes index.
Text in English.
Keywords: Education -- Research; Communication in education; Technical writing; Academic writing -- Publishing; Authorship -- Marketing; Public speaking